2006
DOI: 10.1021/jm0608356
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Sets for Molecular Docking

Abstract: Ligand enrichment among top-ranking hits is a key metric of molecular docking. To avoid bias, decoys should resemble ligands physically, so that enrichment is not simply a separation of gross features, yet be chemically distinct from them, so that they are unlikely to be binders. We have assembled a directory of useful decoys (DUD), with 2950 ligands for 40 different targets. Every ligand has 36 decoy molecules that are physically similar but topologically distinct, leading to a database of 98,266 compounds. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
1,639
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,199 publications
(1,684 citation statements)
references
References 88 publications
(207 reference statements)
20
1,639
1
3
Order By: Relevance
“…The authors of this study reported an improvement of correlation coefficient between calculated and experimental binding energies from 0.347 for the AutoDock calculated binding energies to 0.996 after rescoring. A reason for the lack of improvement in the current study may be the challenging DUD decoy set, which was chosen according to physico-chemical similarity with the known ligands (Huang et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of this study reported an improvement of correlation coefficient between calculated and experimental binding energies from 0.347 for the AutoDock calculated binding energies to 0.996 after rescoring. A reason for the lack of improvement in the current study may be the challenging DUD decoy set, which was chosen according to physico-chemical similarity with the known ligands (Huang et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The present study reveals the first evaluation of the virtual screening performance of the new software AutoDock Vina (Trott & Olson, 2010), the new version of AutoDock 4.2 (Huey et al, 2007) and Gemdock (Yang & Chen, 2004) against a selection of targets from the Database of Useful Decoys (Huang et al, 2006) (DUD). In addition, various strategies of combining the results of two or more docking algorithms were developed and and the utility of recently published ligand efficiency indices (Garcia-Sosa et al, 2010) was evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MQN-calculations are extremely fast and therefore particularly well suited to classify very large databases such as PubChem, which contains over 20 million structures, or the chemical universe database GDB-13 which contains 977 million structures as shown in the following paper in this issue [22][23][24][25]. The MQN-system is also relevant for medicinal chemistry, as illustrated by the fact that similarity searches in MQN-space enrich bioactives in the DUD database [26] from the entire PubChem with efficiencies comparable to that of substructure fingerprints, with the added benefit that lead-hopping relationships between actives are allowed [27].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we selected the Directory of Universal Decoys (DUD) [30] as the source of decoys. In the DUD, there are a total of 15996 decoys that are believed to be non-binders of EGFR TK.…”
Section: Ligand Preparationmentioning
confidence: 99%